Dinamika Aspek Hukum Zakat dan Wakaf di Indonesia - N. Oneng Nurul Bariyah (Universitas Islam Negeri Jakarta, 2016)
The Dynamics of Legal Aspects of Zakat and Waqf in Indonesia. This study shows that the codification of the law of zakat in Indonesia occurs gradually. Codification of Zakat still focuses much on zakat management. Zakat management is undertaken by the National Zakat Board (BAZNAS) and the Amil Zakat Institute (LAZ). The developmental aspects of zakat consist of: amil zakat, muzaki, zakat object, sanctions, and charity as a tax deduction. Meanwhile, the legal codification of waqf in Indonesia experienced significant growth after the enactment of Law Number 41 Year 2004 on Wakaf including: the concept of endowments, wakif, waqf objects, elements of endowments, nazir, waqf institutions (BWI), monitoring, dispute resolution, and criminal sanctions for violations of the waqf objects.DOI: 10.15408/ajis.v16i2.4450